FRI0476 Comorbidities in Psoriatic Arthritis: Patient Education Counts. (15th July 2016) - Aydin, S.Z.; Bayindir, O.; Oksuz, M.F.; Dogru, A.; Kimyon, G.; Tarhan, E.F.; Erden, A.; Yavuz, S.; Can, M.; Cetin, G.Y.; Kilic, L.; Kucuksahin, O.; et al.
Abstract : Background: Comorbidities are frequent in Psoriatic arthritis (PsA) and can have an impact on morbidity and mortality. Objectives: We aimed to investigate the frequency of different comorbidities in PsA, how comorbidities have an impact on PsA features and which factors were associated with the occurrence of comorbidities in a large number of patients, using PsART (Psoriatic Arthritis Registry of Turkey)registry. Methods: PsART is a national, web-based registry where consecutive patients with PsA are recruited and demographic, clinical and therapeutic information are collected as well as comorbidities. The following comorbidities are questioned: Hypertension (HT), hyperlipidemia, depression, diabetes mellitus (DM), hyperuricemia, coronary arterial disease, liver disease, cerebrovascular accident, cancer, and depression. BMI more than 30 is recorded as obesity. Patients with or without comorbidities were compared for their demographic features and outcome tools. Results: One thousand and sixty-nine patients whom comorbidity data were available were analyzed. Within these 693 (64.8%) were women. Mean (SD) age was 46.9 (12.8), with a median (range) PsA duration 45 (0–545) months. The number of patients with 1, 2 and 3 comorbidities were 642 (60.1%), 345 (32.3%), and was 191 (17.9%), respectively. Frequency of comorbidities was obesity in 327 (30.6%), HT in 256 (23.9%), hyperlipidemia in 199 (18.6%), depression in 188 (17.6%), DM in 161 (15.1%), hyperuricemia in 74 (6.9%), coronary artery disease in 39 (3.6%), liver disease 38 (3.6%), cerebrovascular event in 19 (1.8%), and cancer history 16 (1.5%). Patients with at least one comorbidity were older (51.1 (11.8) vs 40.9 (11.7), p<0.001) and had a higher disease activity (according to tender joint count (3.9 (5.2) vs 2.9 (4.2), p=0.001), pain (4.6 (2.6) vs 4.0 (2.6), p=0.006), patient global assessment (4.5 (2.4) vs 4.0 (2.5), p=0.014), fatigue (4.9 (2.5) vs 4.0 (2.6), p<0.001)). Education was found to contribute on comorbidities as patients with at least one comorbidity had less education in terms of school years (7.6 (4.4) vs 9.7 (4.4) years, p<0.001). This was also found separately for some of the comorbidities: Patients with DM (mean (SD) years of education 6.7 (4.2) vs 8.8 (4.5), p<0.001), HT (6.7 (4.3) vs 8.9 (4.5), p<0.001), cerebrovascular event (5.5 (2.9) vs 8.4 (4.5), p=0.012) and depression (7.5 (4.1) vs 8.6 (4.6), p=0.004) had less education compared to patients who don't have those comorbidities. Conclusions: Our registry supported that comorbidities are frequent in PsA increasing the complexity of the disease and have an impact on the disease severity. Patients with comorbidities are less educated showing that education and awareness are important to improve patient outcomes in PsA in long term. Disclosure of Interest: None declared